Testing the behaviour of different inventory control policies in case of extended reverse logistics by using simulation. (1st January 2014) - Longo, Francesco
Nowadays, sustainability issues are stressing the importance of the inventory management problem in case of reverse logistics. The aim of this article is twofold: first it provides the reader with an updated and exhaustive review of the most important inventory control policies to be used when dealing with products return (reverse logistics). Second, the article aims at comparing (by proposing an advanced simulation framework called IMPRES) the behaviour of different inventory control policies (in terms of supply chain costs) extending some of the models proposed in literature in different directions (i.e., disposal option available at any stage of the supply chain, stochastic manufacturing and remanufacturing lead times, multiple return options, multi-echelon inventory systems).